El sismo de 1985 y la deuda externa. Economía política y moral de un desastre - Ramírez de Garay, Iván (El Colegio de México, A.C., 2023)
Primarily based on the historical archives of the World Bank and the International Monetary Fund, this article reconstructs the efforts of the Mexican government to obtain international financing for the reconstruction of Mexico City following the 1985 earthquake. It thus studies the possible influence of these emergency loans on the broader negotiation of the foreign debt, which had reached a critical point by 1985. By reconstructing this situation, this article also seeks to understand the unilateral moratorium demanded by the left and by victims’ groups as a moral demand of a sacrificial nature. Going against the grain of the dominant narratives on this period, it does not reveal a Mexican government aligned with Washington neoliberalism, but one that often skillfully and tenaciously resisted it as part of a much more complex and uncertain process of change in the meaning of government.